Milk derived highly ordered mesoporous carbon with CaF2 nanoclusters as an efficient electrode for supercapacitors. (15th August 2021) - Joseph, Stalin; Lee, Jang Mee; Benzigar, Mercy R.; Yi, Jiabao; Karakoti, Ajay; Vinu, Ajayan
Abstract: Here we report on the synthesis of highly ordered nanoporous carbon decorated with CaF2 nanoclusters along the pore wall structure using dairy milk as a carbon and calcium source through nano-hard templating approach wherein mesoporous silica SBA-15 with different pore diameters are used as template. CaF2 is introduced during the removal process of silica template and can help to enhance the charge transfer. Nitrogen adsorption results reveal that the prepared materials exhibit high specific surface area with bimodal porous structures which act as a media for the rapid ion transports through the regular and interconnected micro- and mesoporous structure. The mesoporous carbon samples also exhibit hexagonally ordered pores with rod shaped morphology, which is similar to that of the template, confirming that the templating process is successful. Finally, the optimised electrode is highly stable and offers the capacitance of 182 F g −1 at 0.5 A g −1 with almost 100% retention rate even after 5000 cycles due to a strong intimate coupling generated by the CaF2 nanoclusters within the wall structure. The electrode performance of milk derived carbon samples is much better than that of activated carbon, multiwalled carbon nanotubes and the mesoporous carbons without CaF2 . Graphical abstract: Image 1